Trachysalambria aspera (Alcock, 1905) (Crustacea, Decapoda, Penaeidae) from the southeastern Arabian Sea, India - Pillai, S. Lakshmi; Jeena, N.s.; Maheswarudu, G.; Sreesanth, L.; Ragesh, N. (Zootaxa, 2021)
Trachysalambria aspera (Alcock, 1905) was first reported and described in detail by Alcock (1905) as Trachypeaneus asper Alcock, 1905, from the Ganjam coast (Odisha, India) and Andaman Sea. Chan et al. (2016) revised the species under the genus Trachysalambria based on molecular genetic data and resolved the confusion in their taxonomy in literature. However, they could not examine the types of T. aspera due to their non-availability (Chan et al. 2016). So we discuss the characters of the species based on the photograph of the type specimen from the Zoological Survey of India, Kolkata with that of Chan et al. (2016) and also with the specimens collected from southwest coast of India where the species has not been reported earlier, but only Trachysalambria curvirostris (George, 1967). Earlier, among Trachysalambria species, T. curvirostris was reported from both the east (Bay of Bengal) and west coasts (Arabian Sea) of Indian waters (Kunju, 1960; George, 1967; Muthu, 1971; Thomas, 1976). Chan et al. (2016) states that T. curvirostris may have a restricted distribution to northern Pacific Ocean.